Conditional Relative Survival of Ovarian Cancer: A Korean National Cancer Registry Study - Shin, Dong Wook; Bae, Jaeman; Ha, Johyun; Jung, Kyu-Won (Frontiers in Oncology, 2021)
Objective: Conditional relative survival (CRS) rates, which take into account changes in prognosis over time, are useful estimates for survivors and their clinicians as they make medical and personal decisions. We aimed to present the 5-year relative conditional survival probabilities of patients diagnosed with ovarian cancer from 1997–2016. Methods: This nationwide retrospective cohort study used data from the Korean Central Cancer Registry. Patients diagnosed with ovarian cancer between 1997 and 2016 were included. CRS rates were calculated stratified by age at diagnosis, cancer stage, histology, treatment received, year of diagnosis, and social deprivation index. Results: The 5-year relative survival rate at the time of diagnosis was 61.1% for all cases. The probability of surviving an additional 5 years, conditioned on having already survived 1, 2, 3, 4, and 5 years after diagnosis was 65.0, 69.5, 74.6, 79.3, and 83.9%, respectively. Patients with poorer initial survival estimates (older, distant stage, serous histology) generally showed the largest increases in CRS over time. The probability of death was highest in the first year after diagnosis (11.8%), and the conditional probability of death in the 2nd, 3rd, 4th, and 5th years declined to 9.4%, 7.9%, 6.1%, and 5.2%, respectively. Conclusion: CRS rates for patients with ovarian cancer improved over time, but did not reach the level of no excess probability of mortality per year even 5 years after diagnosis. The largest improvements in CRS were observed in patients with poorer initial prognoses. Our findings provide updated prognosis to ovarian cancer survivors and clinicians.